2022
DOI: 10.1186/s40560-022-00649-w
|View full text |Cite
|
Sign up to set email alerts
|

Timing of tracheostomy and patient outcomes in critically ill patients requiring extracorporeal membrane oxygenation: a single-center retrospective observational study

Abstract: Background Extracorporeal membrane oxygenation (ECMO) is an integral method of life support in critically ill patients with severe cardiopulmonary failure; however, such patients generally require prolonged mechanical ventilation and exhibit high mortality rates. Tracheostomy is commonly performed in patients on mechanical ventilation, and its early implementation has potential advantages for favorable patient outcomes. This study aimed to investigate the association between tracheostomy timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Early implementation of this strategy remains attractive. Early tracheostomy could also be considered in this context, and has been suggested to improve outcome (83).…”
Section: Discussionmentioning
confidence: 99%
“…Early implementation of this strategy remains attractive. Early tracheostomy could also be considered in this context, and has been suggested to improve outcome (83).…”
Section: Discussionmentioning
confidence: 99%
“…The early initiation of ECMO is believed to have interrupted such a vicious cycle, leading to avoidance of fatal side effects and successful weaning from ECMO. In addition, recent reports have revealed that early tracheostomy after VV ECMO initiation is associated with shorter ECMO support duration and ICU stay and lower hospital mortality rates [ 13 , 14 ]. In this case, the patient underwent tracheostomy on day 5 after VV ECMO initiation and was subsequently weaned off VV ECMO within a short period.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure offers several advantages, including enhanced patient comfort, reduced reliance on sedative agents, accelerated MV weaning, lower incidence of nosocomial pneumonia, and shorter hospital stays [14]. These benefits suggest that an early tracheostomy may have effects on clinical outcomes in patients receiving MV attention [15][16][17][18]. The prospect that patients with long-term MV and tracheostomy may exhibit distinct outcomes underscores the necessity for tailored prognostic models for this specific population.…”
Section: Introductionmentioning
confidence: 99%